Insect Identification Service Instructions for Submitting Samples - Sloderbeck, Phillip E.; Davis, Holly; Phillips, Thomas W. (My University, 2009)
This publication helps individuals send in pests and insects into be identified.
EP162_2009_05
Keywords: EP162; Insects; EP